Essay on a Seaside Enclosure: Transformative Processes of Urban Form and Life - Campos, Martha Machado (Farol, 2025)
This essay links urban history studies to the oldest port sector in the city of Vitória, in the capital’s historic center. It presents, from a historical perspective, iconographic documentation on the area’s transformative processes, divided into periods from colonial Brazil to the 21st century. Considered morphological elements of the city, the delimited enclosure comprised of the edges of Vitória Bay, Oito de Setembro Square, and Vitória Commercial Wharf highlights changes in urban form over time, inextricably linked to the seaside boundary and local ways of life.